Elevated serum eotaxin and IP‐10 levels as potential biomarkers for the detection of esophageal squamous cell carcinoma. Issue 9 (21st July 2021) - Chang, Chen; Wang, Min‐Jie; Bi, Xiao‐Feng; Fan, Zhi‐Yuan; Feng, Dan; Cai, Hong‐Qing; Zhang, Yu; Xu, Xin; Cai, Yan; Qi, Jun; Wei, Wen‐Qiang; Hao, Jia‐Jie; et al.
Abstract: Background and Aims: Esophageal squamous cell cancer (ESCC) is one of the leading malignant cancers with a high incidence and mortality. Exploring novel serum biomarkers will help improve the management and monitoring of ESCC. Methods: In the present study, we first used a ProcartaPlex Array to screen for serum proteins that were increased in 40 ESCC patients compared with matched normal controls; we found that eight proteins (IL‐2, IL‐5, IP‐10, IL‐8, eotaxin, TNF‐α, HGF, and MIP‐1b) had higher serum levels in ESCC patients than in normal controls. We further verified the clinical relevance of the candidate biomarkers with a larger sample of sera. Results: In the 174 tested ESCC patients and 189 normal controls, the serum levels of eotaxin and IP‐10 were significantly higher in patients than in normal controls ( p = 0.0038, 0.0031). In particular, these two proteins were also elevated in the sera of patients with early‐stage (0‐IIA) ESCC ( p = 0.0041, 0.0412). When combining CEA and CYFRA21‐1 (in use clinically) with eotaxin or IP‐10, the effectiveness of detecting ESCC was superior to that of CEA and/or CYFRA21‐1 alone. Moreover, the serum level of eotaxin dropped significantly after surgical resection of primary tumors compared with that in preoperative ESCC samples ( p < 0.001). Conclusions: The data suggest that serum eotaxin and IP‐10 might be potential biomarkers for the detection of ESCC. Abstract : Serum samples from 40 ESCC patients and 40 normal controls were used to screen protein candidates by using ProcartaPlex Array in the biomarker discovery stage. The diagnostic values of the candidate IL‐2, IL‐5, IP‐10, IL‐8, eotaxin, TNF‐α, HGF, MIP‐1b using ELISA were further evaluated in 363 serum samples in the biomarker assessment stage and were finally evaluation value of protein panels for the detection and therapy monitoring of ESCC.